2017
DOI: 10.15252/msb.20177739
|View full text |Cite
|
Sign up to set email alerts
|

An integrated computational and experimental study uncovers FUT 9 as a metabolic driver of colorectal cancer

Abstract: Metabolic alterations play an important role in cancer and yet, few metabolic cancer driver genes are known. Here we perform a combined genomic and metabolic modeling analysis searching for metabolic drivers of colorectal cancer. Our analysis predicts FUT9, which catalyzes the biosynthesis of Ley glycolipids, as a driver of advanced‐stage colon cancer. Experimental testing reveals FUT9's complex dual role; while its knockdown enhances proliferation and migration in monolayers, it suppresses colon cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 68 publications
1
25
1
Order By: Relevance
“…We confirmed the impact of SFTPB UTR mutations by performing a genome-wide association analysis of expression differences and found that samples with SFTPB mutations showed lower RNA abundance in PCDHA7 , a gene known to be involved in cells’ self-recognition and non-self-discrimination (chi-squared p -value 3.6 × 10 -8 ). While other promising candidates exist, such as FUT9 , a fucosyltransferase involved in organ bud progression during embryogenesis and has been implicated in cancer initiation 36 , we found no additional evidence for supporting its driver status.…”
Section: Resultscontrasting
confidence: 85%
“…We confirmed the impact of SFTPB UTR mutations by performing a genome-wide association analysis of expression differences and found that samples with SFTPB mutations showed lower RNA abundance in PCDHA7 , a gene known to be involved in cells’ self-recognition and non-self-discrimination (chi-squared p -value 3.6 × 10 -8 ). While other promising candidates exist, such as FUT9 , a fucosyltransferase involved in organ bud progression during embryogenesis and has been implicated in cancer initiation 36 , we found no additional evidence for supporting its driver status.…”
Section: Resultscontrasting
confidence: 85%
“…Yet, in the human samples we have not detected any significant alteration of FUT4 (Figure 2). Importantly, despite the reported expression of FUT9 in human colon [74], we were unable to detect measureable amount of FUT9 transcript in the colon samples independently of the status of inflammation, despite using three different primer and probe sets (data not shown).…”
Section: Support Of Immune Cell Traffickingmentioning
confidence: 73%
“…In the present study, we exploited the CRISPR-dCas9-VPR system for transcriptional activation of certain α1-3 fucosyltransferase genes, Fut4 (Giordano et al 2015) and Fut9 (Auslander et al 2017), playing a major role in colorectal cancer pathogenesis. According to our findings, transcriptional activation of the Fut4 and Fut9 genes in MC38 cells resulted in specific neo-expression of the Lewis x antigen on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Although different fucosyltransferases are responsible for its synthesis, fucosyltransferase 4 (FUT4) and fucosyltransferase 9 (FUT9) are the most competent ones in synthesizing Lewis x (Mondal et al 2018). Notably, both enzymes are strongly associated with colorectal cancer progression, metastasis and resistance to chemotherapy (Giordano et al 2015, Auslander et al 2017). However, the biosynthetic properties of the FUT4 and FUT9 enzymes and the potential effect of increased Lewis x expression on the glycosylation status of colorectal cancer cells have not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%